Coping dn Difficult Situations as an Area of Preparation of Minors From Resocialization Facilities for Independent Life - Mielczarek, Mirosław (Roczniki Nauk Społecznych, 2025)
The article addresses the issue of one aspect of independence, namely how minors who have been placed in institutional rehabilitation programs by court decision cope with difficult situations. The text is mainly the author’s research, which forms part of a larger, unpublished research project on the independence of minors from juvenile correctional centers. The aim of the presented study was to examine the differences in coping strategies in difficult situations among residents of juvenile correctional centers compared to adolescents from regular schools. The study was exploratory and did not formulate any hypotheses. It was conducted within a pragmatic framework using a diagnostic survey method. The selected method involved a test technique. The author used the Coping with Difficult Situations Questionnaire developed by Andrzej Mirski, which contains 38 descriptions of challenging social situations. The results obtained indicate, among other things, that youth from resocialization facilities preferred more defensive and destructive coping strategies, such as avoidance, aggression, and submission. In contrast, students attending regular schools showed a higher level of the desired strategy, defined as cooperation.